Noninvasive Stool RNA Test Approximates Disease Activity in Patients With Crohn’s Disease - Ryan B. Ghannam; Erica K. Barnell; Ali Osman; Richard Roberts; Patrick Donohue; Spencer King; Jack Land; Clayton Grass; Matthew A. Ciorba; Parakkal Deepak (Gastro Hep Advances)
Background and Aims: Management of Crohn’s disease (CD) requires frequent monitoring for disease activity and response to therapy. In this study, we examined the clinical utility of a novel stool-derived eukaryotic RNA (seRNA)-based diagnostic in patients with CD. Methods: Stool samples were collected from 68 individuals for up to 3 time points prior to, and after initiation of an advanced therapy. Stool samples underwent RNA extraction and sequencing using a custom capture panel (n = 1507 transcripts). seRNA signatures were compared to Crohn's Disease Activity Index scores and endoscopies, when available. Random forest models classified disease severity when compared to Crohn's Disease Activity Index scores. seRNA signatures were also used to assess expression of the therapy target and cell type abundance at various time points. Results: Across all 102 samples collected from 68 individuals, the classifier successfully parsed individuals with active disease (n = 37) relative to those in remission (n = 65) with 87% sensitivity and 77% specificity, respectively. A second classifier, which was employed on subjects with active disease (n = 37), successfully parsed individuals with mild disease (n = 15) from those with moderate disease (n = 22) with 93% and 86% sensitivity, respectively. For the 16 subjects with longitudinal data, seRNA expression of the therapeutic target (eg, ITGA4/ITGB7 for vedolizumab or IL12/IL23 for ustekinumab) as well as lymphocyte burden was correlated with response. Conclusion: A novel seRNA and informatic-based method reliably discriminates active disease from remission and stratifies mild from moderate CD activity. This demonstrates preliminary feasibility to predict therapeutic response and assess disease activity for patients with CD.